DAMPAK PERKEMBANGAN PARIWISATA TERHADAP KEHIDUPAN MASYARAKAT PESISIR KELAPA LIMA, KUPANG - Utari Sterla Tibuludji; Made Sudiana Mahendra; I Made Adhika (Magister Tourism Study, Faculty of Tourism, Udayana University, 2017)
The development of tourism sector in Kupang for the last 10 years is concentrated in coastal region of Kupang Bay. The life style of coastal communities in Kelapa Lima before tourism was traditional and rely on nature, is now begin to change as the impact of tourism development on their life environment. The aim of this article is to analyze the impact of tourism on the quality of life of coastal communities of Kelapa Lima. The method being used in this research was descriptive qualitative and quantitative method (mixed methods research). Theory being used was Tourist Area Life Cycle. Data analysis technique was using descriptive qualitative data analysis. Presentation of data analysis result was conducted formally and informally. The result of research outlined the quality of life of coastal communities at Kelapa Lima Kupang before and after tourism developed, corresponding to 7 indicators quality of life according to OECD namely income, residence, environment, social stability, health, education and job opportunity. The role of tourism related to improvement the quality of life of coastal communities by revamping and structuring coastal area, the opening of new job opportunities, and creativity development of industrial and household output.